Digital competency and self-efficacy as drivers of innovative behavior among displaced workers in post-pandemic Indonesia - Sinaga, Eduard; Wijoyo, Suparto; Lestary, Yetty Dwi; Indaryanto, Adrid; Harijadi, Bambang Dwi (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
The COVID-19 pandemic has accelerated digital transformation in the world of work, requiring individuals to have qualified digital competencies and high innovative capacity. This study aims to analyze the relationship between self-efficacy and digital competence on innovative behavior, with absorptive capacity as a mediating variable. This study also responds to the literature gap regarding the mediating role of absorptive capacity in the post-pandemic context. A quantitative approach was used with a survey method of 250 respondents. Data were analyzed using Partial Least Square Structural Equation Modeling (PLS-SEM) technique. The results showed that self-efficacy and digital competence have a positive and significant effect on innovative behavior. Absorptive capacity was shown to mediate the relationship between self-efficacy and innovative behavior, but did not mediate the relationship between digital competence and innovative behavior. These findings provide important practical implications for organizations in strengthening a post-pandemic culture of innovation. This research highlights the importance of building self-efficacy, increasing digital competence and strengthening absorptive capacity to foster innovative adaptation amid digital disruption.